(untitled) (Swiss Medical Weekly, 2021)
BACKGROUND We aimed to analyse the nodal spread of our non-small cell lung cancer pN2 cohort according to tumour location, the possible implications of an unusual spreading pattern, and other factors influencing postoperative survival after anatomical lung resection. METHODS In this retrospective observational study, clinical data was collected for 124 consecutive non-small cell lung cancer (NSCLC) patients with a pathological N2 (stage IIIA or B) undergoing anatomical lung resection at our institution between 2001 and 2010. Cox regression was used to analyse independent predictors of 5-year overall survival and recurrence-free survival. RESULTS A total of 105 patients were included in the final analysis. Tumour location in the right upper lobe and middle lobe was significantly more often associated with involvement of lymph node stations 2 and 4 than NSCLC in the right lower lobe (station 2: right upper vs right lower lobe, p = 0.001 and middle vs right lower lobe, p = 0.038; station 4: right upper vs right lower lobe, p<0.001 and middle vs right lower lobe, p = 0.056), while tumours in the right upper lobe showed significantly less involvement of stations 7 and 8 compared with right lower lobe tumours (station 7 p <0.001, station 8 p = 0.004). Left sided tumours in the upper lobe had significantly more involvement of station 5 compared to lower lobe tumours (p = 0.009). However, atypical lymphatic nodal zone involvement did not emerge as a significant predictor of survival. Lymphovascular invasion was the only independent prognostic factor for 5-year overall survival (hazard ratio [HR] 2.10, p = 0.015) and recurrence-free survival (HR 1.68, p = 0.049) when controlled for adjuvant therapy. CONCLUSION Lymphovascular invasion was identified as the only independent prognostic factor for 5-year overall survival and recurrence-free survival in our pathologically proven N2 NSCLC cohort when controlled for adjuvant therapy. This study extends the current evidence of an adverse prognostic effect of lymphovascular invasion on a stage III population, confirms the adverse prognostic effect of lymphovascular invasion detected by immunohistochemistry, and thereby reveals another subgroup within the pN2 population with worse prognosis regarding 5-year overall survival and recurrence-free survival.